a n = n − 1 n + 1 ( a 1 + a 2 + a 3 + … + a n − 1 )
Consider the recurrence relation above for n ≥ 2 and a 1 = 1 .
If a 2 0 1 5 = b × 2 d , where b is an odd integer, then find b + 2 + d .
Note : This problem can be solved without any calculator aids.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Equivalently a n = ( n + 1 ) ⋅ 2 n − 2 .
Let
S n = a 1 + a 2 + . . . + a n
a n = S n − S n − 1
Then we can rewrite equation as:
S n − S n − 1 = n − 1 n + 1 S n − 1
S n = n − 1 2 n S n − 1
Now you can easily see that:
S n = n − i 2 i n S n − i
Putting i = 1 and S 1 = 1 you can calculate:
S 2 0 1 5 = 2 2 0 1 4 2 0 1 5 and S 2 0 1 4 = 2 2 0 1 3 2 0 1 4
And you will get:
a n = 6 3 ˙ 2 2 0 1 8
Problem Loading...
Note Loading...
Set Loading...
a n − 1 = n − 2 n ( a 1 + a 2 + a 3 + . . . + a n − 2 ) From which it follows that: a 1 + a 2 + a 3 + . . . + a n − 2 = n n − 2 ⋅ ( a n − 1 ) a n = n − 1 n + 1 ( a 1 + a 2 + a 3 + . . . + a n − 2 + a n − 1 ) a n = n − 1 n + 1 [ n n − 2 ⋅ ( a n − 1 ) + a n − 1 ] a n = n 2 ( n + 1 ) ⋅ a n − 1
The previous equation gives a telescoping product for a n such that a 2 0 1 5 = 2 ⋅ 2 0 1 5 ! 2 2 0 1 4 ⋅ 2 0 1 6 ! = 2 0 1 6 ⋅ 2 2 0 1 3 = 6 3 ⋅ 2 2 0 1 8 Finally, b + c + d = 6 3 + 2 + 2 0 1 8 = 2 0 8 3 .